The Acceptance of Bitcoin in Indonesia Using Technology Acceptance Model - Kumpajaya, Aswinnur; Dhewanto, Wawan (Journal of Business and Management, 2015)
Abstract. In 2009, the world’s first completely decentralized digital currency Bitcoin was introduced by an pseudonymus programmer known as Satoshi Nakamoto. The hype of a novel currency subsequently motivates research on this phenomenon, especially focusing on what affects individuals to use Bitcoin.This paper attempts to address the issue by creating a model of technology acceptance that fits the specific and unique characteristics of the Indonesian environment by extending the Technology Acceptance Model (TAM). We incorporated the Perceived Compatibility from Innovation Diffusion Theory by Everett Rogers (1962) and added Bitcoin Knowledge, and Perceived Risk as additional external variables for TAM. The data are collected through 108 user of Bitcoin from various online forums in Indonesia and was analyzed using Partial Least Square (PLS) path modelling.The results suggested that indeed the perceived compatibility and knowledge affects user’s intention towards Bitcoin. The findings of this study can prove to be useful for Bitcoin community and exchange service in formulating strategies to increase user base and contributes the literature by formulating and validating TAM to predict Bitcoin adoption. Keywords: Technology Acceptance Model, Bitcoin, Extending TAM, Innovation Diffusion, Compatibility, Risk, Indonesia.